Review of the exploring spatial visualisation and gender among 3d computer animation undergraduates - Che din, Sharkawi; Abdul Wahab, Nurulakma; Abu Sujak, Farhanah (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
The performance of multimedia undergraduates in 3D computer animation may be impacted by their deficiencies in spatial visualisation. It is possible to see spatial visualisation as a distinct intelligence that differentiates it from other types, such as verbal and reasoning abilities. Creating a 3D animation required complex visualisation work, which most students found challenging. Students who cannot finish the task due to inadequate spatial visualisation skills will not be able to pass the 3D computer animation course. This study investigates the relationship between undergraduates' performance in 3D computer animation, gender, and spatial visualisation. The first stage of the research was to examine the literature related to spatial visualisation, gender differences and computer animation skills among undergraduate students.